2005
DOI: 10.1016/j.jsgi.2004.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Polymorphonuclear Leukocyte Priming Contributes to Oxidative Stress in Early Pregnancy

Abstract: The increased PMNL count is probably a compensatory response to PMNL priming. The increased rate of superoxide release from primed PMNL may contribute to oxidative stress in early pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Neutrophils from preeclamptic patients produce enhanced levels of ROMs (42), which probably contribute to oxidative stress (43). Although syncytiotrophoblasts derived from normal pregnant women deactivate neutrophil ROM production in this study, syncytiotrophoblasts from patients with severe preeclampsia stimulate neutrophil superoxide production (44).…”
Section: Discussionmentioning
confidence: 56%
“…Neutrophils from preeclamptic patients produce enhanced levels of ROMs (42), which probably contribute to oxidative stress (43). Although syncytiotrophoblasts derived from normal pregnant women deactivate neutrophil ROM production in this study, syncytiotrophoblasts from patients with severe preeclampsia stimulate neutrophil superoxide production (44).…”
Section: Discussionmentioning
confidence: 56%
“…25 Early pregnancy is characterized by a rise in the count of activated peripheral polymorphonuclear leukocytes, which accounts for the increased generation of reactive oxygen species. 26 Low levels of plasma CoQ 10 were observed in spontaneous abortion and threatened abortion as compared to normal pregnancy. 16 Also, in a placebo-controlled trial, it had been observed that CoQ 10 supplementation during pregnancy reduces the risk of developing preeclampsia in women.…”
Section: Discussionmentioning
confidence: 97%
“…We studied the population of total helper T cells by gating CD3 + CD4 + T cells in the peripheral blood lymphocytes of RPL and normal pregnant females. No significant difference was observed in the proportion of CD3 + CD4 + T cells in pregnant RPL females and that of the healthy pregnant females [25.5 versus 26.45] ( Fig. 1a).…”
Section: Proportion Of Th1-and Th2-type Lymphocytes In Pregnant Womenmentioning
confidence: 98%
“…However, the enzyme content may be lowered in the neutrophils of the patients with specific granule deficiency [ 23 ] or elevated in pregnant women [ 24 ]. Reduced or absent NAP activity is also found in neutrophils from patients with chronic myeloid leukemia [ 25 ].…”
Section: Discussionmentioning
confidence: 99%